Happy birthday, Addy! : a springtime story - Porter, Connie Rose, 1959-; Taylor, Dahl (Middleton, Wis. : Pleasant Co., 1998)
In the spring of 1865, Addy finds inspiration from a new friend and chooses a birthday for herself as she and her parents try to shape a new life of freedom in Philadelphia despite the racial prejudice they encounter throughout the city.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Prejudices -- Fiction; Friendship -- Fiction; Birthdays -- Fiction; Slavery -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction